Analisis Perilaku Tanggung Jawab dalam Pembelajaran PKn Siswa Kelas IV SD Negeri Cipondoh 2 Kota Tangerang - Safitri, Indah; Sa’odah, Sa’odah; Magdalena, Ina (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2020)
Behavior Analysis of Responsibility in Learning PKn Class IV Students of SD Negeri Cipondoh 2 Tangerang City. Faculty of Teacher Training and Education, University of Muhammadiyah Tangerang 2020. This research is a descriptive qualitative research by taking data at SD Negeri Cipondoh 2 Tangerang City with the subject of teacher research. Data analysis was carried out through observation, interviews, questionnaires and documentation. Data analysis was carried out by collecting data, reducing data, presenting data that draw conclusions. The results showed that the analysis of responsibility behavior in PKn lessons at SD Negeri Cipondoh 2 Kota Tangerang was seen from data collection carried out through observation, interviews, questionnaires and documentation that: Analysis of responsibility behavior in PKn lessons, students are less responsible in lessons, it can be seen that the teacher must increase the responsibility of students in lessons in the classroom and outside the classroom.